Case report: Recurrent glossopharyngeal neuralgia after previous glossopharyngeal rhizotomy: Microvascular decompression with intra-operative neurophysiology. (2nd November 2015) - Price, Sally-Ann S.; Davies, Owain; Walsh, Peter; Patel, Nikunj
Abstract : We present a case of recurrent vago-glossopharyngeal neuralgia after previous surgery, treated successfully with microvascular decompression using intra-operative neurophysiology monitoring.